Pelatihan Aplikasi Cisco Packet Tracer Sebagai Media Simulasi Pembuatan Jaringan di Smp Islam Nurul Falah - Muhammad Adli Firjatullah; Aip Khaerul Anwar; Airiza Dino Ardanto; Akmal Dwi Syahputra; Dicky Wahyudi; Fajar Renaldi; Iklillatul Aliliyah; Muhammad Nur Rizky; Muhammad Rayhan Saputra; Nasya Nafafil (Abdi Jurnal Publikasi, 2024)
Training on Using the Cisco Packet Tracer Application as a Simulation Media for Network Creation in Schools at Islamic Middle School Nurul Falah Pagedangan. Improving information and communication technology (ICT) skills is a crucial need in the current digital era. One important aspect of ICT is the creation of computer networks. Therefore, this research aims to provide effective training in the use of the Cisco Packet Tracer application as a network creation simulation medium at Nurul Falah Pagedangan Islamic Middle School. The research method used is a practical training approach with a focus on the application of computer network theory and device configuration with Cisco Packet Tracer. The training participants involved teachers and students at Nurul Falah Pagedangan Islamic Middle School. During the training, participants will be equipped with basic networking knowledge, configuring switches and other network devices using Cisco Packet Tracer. It is hoped that the results of this training will increase the participants' understanding in designing, managing and maintaining computer networks. Apart from that, it is also hoped that it will be able to provide practical experience that can be applied in everyday life and increase students' competitiveness in the field of technology. Through this training, it is hoped that Nurul Falah Pagedangan Islamic Middle School can become an educational institution capable of producing reliable graduates in the field of information technology, and can contribute positively to developing human resource potential in the field of technology at the local and national levels.